A STRUCTURED APPROACH TO FOSTERING A HEALTHY PUBLISHING CULTURE FOR CASE REPORTS IN THE DERMATOLOGY DEPARTMENT AT MBARARA UNIVERSITY OF SCIENCE AND TECHNOLOGY: BRIDGING THE PUBLICATION GAP. - Mundeli, Simon Peter; Mohamed , Abdirahman Salad (Student's Journal of Health Research Africa, 2024)
Established in 1998, the Georg Klingmüller Clinic at Mbarara Regional Referral Hospital (MRRH) is Uganda's only center for specialized dermatology training. Despite its role as a center of excellence in specialist dermatologic care and training, there is a notable lack of published case reports from the dermatology clinic at MUST, creating a knowledge gap with resulting diagnostic challenges, particularly in the rare presentation of some dermatoses. This article guides how dermatology postgraduate students at MUST can publish their case studies. It outlines the process from case presentation to drafting and submitting manuscripts, emphasizing the importance of selecting suitable journals and adhering to publication guidelines. The article also highlights the benefits of a robust publication culture, including improved diagnostic accuracy, career advancement opportunities, and enhanced global collaboration. By fostering a healthy publication environment, students can contribute valuable knowledge to the field and advance their professional development.